1980
DOI: 10.3382/ps.0590681
|View full text |Cite
|
Sign up to set email alerts
|

Cage Brooding Followed by Floor Grow-Out: A Technique for Rearing Broilers ,

Abstract: Broiler chicks were maintained in Petersime brooding batteries for three weeks and then transferred to floor pens in a conventional broiler facility for five additional weeks. Hatchmates were reared in floor pens for eight weeks. Comparisons of growth, feed efficiency, carcass quality, and a survey of physiological fitness of both treatment groups were made. The battery brooded birds exhibited lower final body weights and lower feed conversion ratios than the floor reared birds. Differences in mortality, gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1994
1994

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
(8 reference statements)
0
1
0
Order By: Relevance
“…This value was based on theoretical consideration of the height and weight of chickens of different ages and not experimentally tested. Thaxton et al (1980) found 190 cm 2 /chick to give growth comparable to 280 or 370 cm 2 / chick for 3 weeks. Deaton et al (1981) found that growing chicks at densities of 186 and 287 cm 2 /chick for 14 and 21 days, respectively, did not adversely affect 49-day broiler weights.…”
Section: Discussionmentioning
confidence: 90%
“…This value was based on theoretical consideration of the height and weight of chickens of different ages and not experimentally tested. Thaxton et al (1980) found 190 cm 2 /chick to give growth comparable to 280 or 370 cm 2 / chick for 3 weeks. Deaton et al (1981) found that growing chicks at densities of 186 and 287 cm 2 /chick for 14 and 21 days, respectively, did not adversely affect 49-day broiler weights.…”
Section: Discussionmentioning
confidence: 90%